2018
DOI: 10.1097/pai.0000000000000464
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CAS/CSE1L, the Cellular Apoptosis Susceptibility Protein, Correlates With Neoplastic Progression in Barrett’s Esophagus

Abstract: These findings show changes in CAS/CSE1L during BE progression. CAS/CSE1L may represent a potential marker for dysplasia/carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The relation between CSE1L and digestive tract tumors have been reported previously in a many research (Ayham et al, 2012;Jiang et al, 2016;Liao et al, 2008). The expression of CES1L was closely associated with pathological stages, tissue types, and neoplastic progression (Ayham et al, 2012).…”
Section: Discussionsupporting
confidence: 61%
“…The relation between CSE1L and digestive tract tumors have been reported previously in a many research (Ayham et al, 2012;Jiang et al, 2016;Liao et al, 2008). The expression of CES1L was closely associated with pathological stages, tissue types, and neoplastic progression (Ayham et al, 2012).…”
Section: Discussionsupporting
confidence: 61%
“…CSE1L silencing could induce apoptosis and repress the proliferation and invasion of gastric cancer cells by regulating the PI3K/Akt/mTOR and MEK/ERK signaling pathways ( 18 ). In addition, a recent study revealed that the abnormal expression of CSE1L was correlated with neoplastic progression in Barrett’s esophagus ( 19 ). However, the role of CSE1L has not been studied in esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we used microRNA target predictions starBase and identified gene targets associated with cell proliferation and apoptosis in NPC. One such predicted target, CSE1L , has been demonstrated to modulate tumor malignancy in various cellular models [ 15 , 18 , 20 , 47 ], and it is highly expressed in NPC cells [ 21 , 22 , 41 ]. However, it is not clear whether interaction between miR-451a and CSE1L accounts for the tumor-suppressive effects observed in NPC.…”
Section: Discussionmentioning
confidence: 99%